Analysis of the Impact of Islamic Religious Education Learning on Student Character - Syafnan; Irdayani LUBIS; Amron HASIBUAN (RADINKA JAYA UTAMA PUBLISHER, 2025)
This study aims to analyze the impact of Islamic Religious Education (IRE) learning on students' character development at SMA Negeri 4 Sibolga. Character education is a crucial element in the national education system, particularly in shaping students into individuals who are religious, honest, disciplined, responsible, and cooperative. This research employed a descriptive quantitative approach using a survey method, with questionnaires distributed to 60 eleventh-grade students. The results indicate that IRE learning has a positive influence on students' character formation. The religious aspect scored the highest (88%), followed by responsibility (81%) and honesty (79%). Meanwhile, cooperation (72%) and discipline (74%) were identified as areas needing further enhancement through more participatory teaching methods. These findings support the view that IRE is a strategic tool for strengthening character education in secondary schools. Therefore, innovative, contextual, and applicable teaching approaches are needed to ensure optimal internalization of character values among students.